Sensor Fabrication Method for in Situ Temperature and Humidity Monitoring of Light Emitting Diodes - Chi-Yuan Lee; Ay Su; Yin-Chieh Liu; Pin-Cheng Chan; Chia-Hung Lin (Sensors, 2010)
In this work micro temperature and humidity sensors are fabricated to measure the junction temperature and humidity of light emitting diodes (LED). The junction temperature is frequently measured using thermal resistance measurement technology. The weakness of this method is that the timing of data capture is not regulated by any standard. This investigation develops a device that can stably and continually measure temperature and humidity. The device is light-weight and can monitor junction temperature and humidity in real time. Using micro-electro-mechanical systems (MEMS), this study minimizes the size of the micro temperature and humidity sensors, which are constructed on a stainless steel foil substrate (40 μm-thick SS-304). The micro temperature and humidity sensors can be fixed between the LED chip and frame. The sensitivities of the micro temperature and humidity sensors are 0.06 ± 0.005 (Ω/°C) and 0.033 pF/%RH, respectively.